Longitudinal assessment of gait quality in children with bilateral cerebral palsy following repeated lower limb intramuscular Botulinum toxin-A injections - Read, F.; Boyd, Roslyn; Barber, L. (Pergamon Press, 2017)
Background: Serial lower limb intramuscular Botulinum toxin-A (BoNT-A) injections are administered to children with bilateral spastic cerebral palsy (BCP) to reduce spasticity, improve walking and functional mobility, and delay the need for orthopaedic surgery. Gait quality is clinically assessed following BoNT-A with 2D video gait assessments (2DVGA) using the Edinburgh Visual Gait Score (EVGS). Aim: To determine the effect of three consecutive treatment cycles of lower limb intramuscular BoNT-A injections on gait quality using the EVGS in children with BCP by retrospectively reviewing repeated 2DVGA measures. Methods and procedures: Seventeen children with BCP and dynamic equinus (8 females and 9 males, age mean (SD), 4.0 (2.2) years, GMFCS I = 2 and II = 15) were included in the study after a retrospective audit of the records of the Queensland Children’s Gait Laboratory (QCGL), Children’s Health Queensland, Brisbane. The medical records of children who attended the QCGL between January 2001 and January 2016 were searched for eligibility. Children who had undertaken pre- and post-treatment 2DVGA for the first three lower limb BoNT-A treatment cycles (6 assessments) were reviewed using the EVGS. BoNT-A treatments were administered 7.7 (2.3) months apart and post-BoNT-A reviews occurred 12.6 (6.7) weeks after injection. Mixed-effects linear regression assessed the change from baseline to each subsequent assessment (p < 0.05). Outcomes and results: EVGS reduced significantly by a mean of 2.4 points from pre- to post-BoNT-A in the first treatment cycle (p = 0.001). Compared to baseline, mean total EVGS reduced significantly during the second (pre-BoNT-A −1.7 (p = 0.020), post BoNT-A −2.8 (p < 0.001)) and third (pre-BoNT-A −2.6 (p = 0.001), post BoNT-A −2.4 (p = 0.002)) treatment cycles. There was no difference in EVGS between post-BoNT-A in the first treatment cycle and scores for the second and third treatment cycles. Conclusions and implications: Improvements in gait quality were statistically significant, but did not reach the EVGS smallest real difference value of 4 points. Repeated lower limb intramuscular BoNT-A injections to improve gait quality in children with BCP should be reconsidered.